An overview on safety issues related to hydrogen and methane blend applications in domestic and industrial use. (September 2017) - de Santoli, Livio; Paiolo, Romano; Lo Basso, Gianluigi
Abstract: The share of electrical energy hailing from renewable sources in the European electricity mix is increasing. The match between renewable power supply and demand has become the greatest challenge to cope with. Gas infrastructure can accommodate large volumes of electricity converted into gas whenever this supply of renewable power is larger than the grid capacity or than the electricity demand. The Power-to-Gas (P2G) process chain could play a significant role in the future energy system. Renewable electric energy can be transformed into storable hydrogen via electrolysis and subsequent methanation. The aim of this paper is to provide an overview of the required technical adaptations of the most common devices for end users such as heating plants, CHP systems, home gas furnaces and cooking surfaces, wherever these are fuelled with methane and hydrogen blends in variable percentages by volume. Special attention will be given to issues related to essential safety standards, firstly comparing existing Italian and European regulations in this regard, and secondly highlighting the potential need for legislation to regulate the suitability of hydrogen methane blends. Finally, a list of foreseeable technical solutions will be provided and discussed thoroughly.